2015
DOI: 10.1007/s11255-015-1109-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease and its association with cardio-metabolic risk factors in the adult Romanian population: the PREDATORR study

Abstract: The PREDATORR study showed a high prevalence of chronic kidney disease in the adult Romanian population providing data on its prognosis and association with several cardio-metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Of this, 12 studies assessed obesity based on body mass index (BMI), 9,28,36,43,45,56,65,71,72,76,79 ,83 and 35 studies used waist circumference for the assessment of obesity. 12,21,23,24,26,27,[33][34][35][38][39][40]42,44,47,48,[51][52][53][54][55][57][58][59][60][61][62][63][64]67,69,[73][74][75]82 The overall CKD risk related to higher BMI/waist circumference, as compared with lower BMI/waist circumference, was 1.22 (95% CI = 1.12-1.31), and was greater for higher values of waist circumference than BMI (Figure 3). In the stratified analysis by ethnicity, sex, and study type, the increased risk associated with higher values of BMI/waist circumference was significant in different subgroups.…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of this, 12 studies assessed obesity based on body mass index (BMI), 9,28,36,43,45,56,65,71,72,76,79 ,83 and 35 studies used waist circumference for the assessment of obesity. 12,21,23,24,26,27,[33][34][35][38][39][40]42,44,47,48,[51][52][53][54][55][57][58][59][60][61][62][63][64]67,69,[73][74][75]82 The overall CKD risk related to higher BMI/waist circumference, as compared with lower BMI/waist circumference, was 1.22 (95% CI = 1.12-1.31), and was greater for higher values of waist circumference than BMI (Figure 3). In the stratified analysis by ethnicity, sex, and study type, the increased risk associated with higher values of BMI/waist circumference was significant in different subgroups.…”
Section: Obesitymentioning
confidence: 99%
“…The relationship between HDL-cholesterol level and CKD risk was examined in 45 studies, 9,12,21,23,24,[26][27][28][33][34][35][36][38][39][40]42,44,48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][71][72][73][74][75][76]79,82,83 including 692 780 patients and 11 039 480 participants. In the overall analysis, the risk estimate for lower values of HDL-cholesterol, as compared with higher values, was 1.20 (95% CI = 1.11-1.30).…”
Section: Reduced Hdl-cholesterolmentioning
confidence: 99%
“…In other studies, Ashar Alam et al, which looked at the prevalence and risk factors of kidney disease in urban Karachi, 350 patients were studied, of which, 91.4% were nondiabetic showed that 54.3% patients had dyslipidaemia. 3 M. Mota et al in their study 4 looked at cardiometabolic parameters in nondiabetic patients with chronic kidney disease in Romania, and in this study, dyslipidaemia was present in 90%. Hence, the findings in our study were somewhere in between the results obtained by the other authors.…”
Section: Discussionmentioning
confidence: 75%
“…The only metabolic profile parameters which correlated significantly with insulin resistance were HDL-cholesterol with HOMA-IR (r = -0.24, p = 0.007), triglycerides with HOMA C-peptide (r = 0.19, p = 0.03) and uric acid with HOMA C-peptide (r = 0.28, p = 0.001). These results bear clinical relevance in themselves but also in light of diabetics' known predisposition to developing long term complications such as chronic kidney disease (CKD), in which case levels of HOMA-IR, uric acid and triglycerides tend to be higher or even predict CKD [11].…”
Section: Resultsmentioning
confidence: 89%